The science of religion : a defence : essays by Donald Wiebe - Wiebe, Donald, 1943- (Supplements to Method & Theory in the Study of Religion, 2018)
Donald Wiebe, Professor of Philosophy of Religion at Trinity College, University of Toronto, has spent much of his academic career arguing for a clear demarcation between Theology and Religious Studies. The Science of Religion: A Defence offers a brilliant overview of Professor Wiebe's contributions on methodology in the academic study of religion, of the development of his thinking over time, and of his intellectual commitment to 'a science of religion'. The work is divided into three parts. The first part identifies pertinent connections between 'religion', 'religious studies', and 'science' and why 'reductionism' in the academic study of religion, when properly applied, can bridge the explanatory gap between the sceptic and the devotee. The second part treats conceptual debates in the academic study of religion, with particular reference to the place of 'belief', 'understanding', and 'meaning' in the modern study of religion. The third part addresses the theological resistance to the scientific study of religion and how that resistance can be overcome. Finally, two new essays are included: a critique on 'The Preconceptions of a Science of Religion' by Anthony J. Palma, and an accompanying reply by Donald Wiebe. The Science of Religion: A Defence is an essential resource for both scholarly and non-scholarly audiences alike, and will be of particular interest to both defenders and critics of a scientific study of religion.